2017
DOI: 10.1038/s41598-017-01349-4
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus D68 Subclade B3 Strain Circulating and Causing an Outbreak in the United States in 2016

Abstract: In 2014 the United States experienced a nationwide outbreak of Enterovirus D68 (EV-D68) infection. There were no confirmed cases of EV-D68 in 2015 and CDC was only aware of limited sporadic EV-D68 detection in the US in 2016. In this report, we analyzed 749 nasopharyngeal (NP) specimens collected in 2015 and 2016 from patients in the Lower Hudson Valley, New York using a previously validated EV-D68-specific rRT-PCR assay. EV-D68 was detected in none of 199 NP specimens collected in 2015, and in one of 108 (0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 32 publications
7
74
0
Order By: Relevance
“…Recently, the evolutionary analyses performed on complete genome sequences have suggested that subclade B3 was not originated by a mutation occurred on subclade B1 strains. Indeed, it has been suggested a distinct evolutionary origin for the new B3 subclade [45]. Multiple clades of EV-D68 have worldwide circulated simultaneously between 2005 and 2014 [9], while a predominance of one clade (subclade B3) has recently been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the evolutionary analyses performed on complete genome sequences have suggested that subclade B3 was not originated by a mutation occurred on subclade B1 strains. Indeed, it has been suggested a distinct evolutionary origin for the new B3 subclade [45]. Multiple clades of EV-D68 have worldwide circulated simultaneously between 2005 and 2014 [9], while a predominance of one clade (subclade B3) has recently been observed.…”
Section: Discussionmentioning
confidence: 99%
“…EV-D68 cases have been increasing in frequency and severity over the last decade, with outbreaks in the US in 2014 and 2016 (Midgley et al, 2015; Wang et al, 2017). It is likely that the number of cases is severely under-reported, as only the most severe clinical presentations are tested for EV-D68, allowing many infections to go undetected as asymptomatic or mild flu-like cases (Oberste et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, from August 2014 to January 2015, a nationwide outbreak of EV-D68 infection occurred in the United States, resulting in 1,153 con rmed cases including 14 deaths 8,9 . EV-D68 outbreaks were also witnessed in the United States in 2016 and in 2018 10,11 , coinciding with the occurrence of 153 and 237 AFM cases, respectively 12 . In addition, an upsurge of EV-D68 infection was reported in several European countries in 2016 13,14,15 , accompanied by the identi cation of 29 EV-D68associated AFM cases 16 .…”
Section: Introductionmentioning
confidence: 94%